2013
DOI: 10.1530/joe-12-0579
|View full text |Cite
|
Sign up to set email alerts
|

Cephalic phase insulin secretion is KATP channel independent

Abstract: Glucose-induced insulin secretion from pancreatic b-cells critically depends on the activity of ATP-sensitive K C channels (K ATP channel). We previously generated mice lacking Kir6.2, the pore subunit of the b-cell K ATP channel (Kir6.2 K/K ), that show almost no insulin secretion in response to glucose in vitro. In this study, we compared insulin secretion by voluntary feeding (self-motivated, oral nutrient ingestion) and by forced feeding (intra-gastric nutrient injection via gavage) in wild-type (Kir6.2 C/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 33 publications
0
17
1
Order By: Relevance
“…For example, an increase in cytosolic ATP and closure of K ATP channels does not always correlate with insulin output in GSIS [10]. Beta cells can also secrete insulin independently of K ATP channel closure by an unclear mechanism that still requires calcium influx and membrane depolarisation [10,14]. Furthermore, K ATP channel activity can be recorded from oncell patches on beta cells exposed to glucose-free solutions, despite the fact that the intracellular ATP concentration under similar conditions would predict the channels to be closed [15].…”
Section: Introductionmentioning
confidence: 99%
“…For example, an increase in cytosolic ATP and closure of K ATP channels does not always correlate with insulin output in GSIS [10]. Beta cells can also secrete insulin independently of K ATP channel closure by an unclear mechanism that still requires calcium influx and membrane depolarisation [10,14]. Furthermore, K ATP channel activity can be recorded from oncell patches on beta cells exposed to glucose-free solutions, despite the fact that the intracellular ATP concentration under similar conditions would predict the channels to be closed [15].…”
Section: Introductionmentioning
confidence: 99%
“…Preganglionic fibers transverse the vagus and enter the pancreas, 54 terminating in intrapancreatic ganglia from which postganglionic fibers emerge to innervate the Langerhans islets. 55 Studies performed in animals and humans demonstrated that CPIR is independent of ATP-sensitive potassium channels 56 and can be abolished by vagotomy 57 or ganglionic blockade with muscarinic antagonists, 58 which reinforces that this stimulus is mediated by cholinergic neurons of the parasympathetic nervous system. However, in humans, there is evidence that CPIR is also mediated by noncholinergic mechanisms.…”
Section: Cephalic Phase Of Insulin Response and Its Relevance To Metamentioning
confidence: 87%
“…Standard rodent normal chow, dextrin, and high-sucrose diet were used as previously reported , Seino et al 2013. Dextrin hydrate, glimepiride, diazoxide, a-methyl-D(C)-glucoside (aMG) were purchased from Wako, Osaka, Japan.…”
Section: Methodsmentioning
confidence: 99%
“…As described previously (Seino et al 2013), both Kir6.2 C/C and Kir6.2 K/K mice were trained for the experiments of voluntary feeding with standard chow or dextrin. They were deprived of food for 16 h and then given free access to standard chow or dextrin for the voluntary feeding experiments.…”
Section: Voluntary Feedingmentioning
confidence: 99%